Effects of the genetic knockout of the β-1, 3-galactosyltransferase 2 on spatial learning and neurons in the adult mouse hippocampus and somatosensory cortex. Issue 1 (14th November 2022) - Chen, Xiaojie; Wang, Pan; Ren, Lili; Deng, Xinyang; Yin, Xuechen; Zhang, Luyun; Li, Qingyu; Bai, Lina; Li, Xiaojia; Wang, Peng; Bi, Jing
Abstract : Objective: Glycosyltransferases contribute to the biosynthesis of glycoproteins, proteoglycans and glycolipids and play essential roles in various processes in the brain, such as learning and memory, brain development, neuronal survival and neurodegeneration. β-1, 3-galactosyltransferase 2 (B3galt2) belongs to the β-1, 3-galactosyltransferase gene family and is highly expressed in the brain. Recent studies have indicated that B3galt2 plays a vital role in ischemic stroke through several signaling pathways in a mouse model. However, the function of B3galt2 in the brain remains poorly understood. Methods: The genotypes of mice were determined by PCR. To verify B3galt2 expression in an adult mouse brain, X-gal staining was performed in 6-month-old B3galt2 heterozygous ( B3galt2 +/− ) mice. Using adult B3galt2 homozygous ( B3galt2 −/− ), heterozygous and wild-type (WT) littermates, spatial learning and memory were determined by the Morris Water Maze test, and neurotoxicity and synaptic plasticity were examined by immunofluorescence. Results: B3galt2 was highly expressed in the adult mouse hippocampus and cortex, especially in the hippocampal dentate gyrus. Compared to that of WT mice, the spatial learning ability of adult B3galt2 −/− mice was impaired. B3galt2 mutations also caused neuronal loss and synaptic dysfunction in the hippocampus and somatosensory cortex, and these changes were more obvious in B3galt2 −/− mice than in B3galt2 +/− mice. Conclusions: The findings indicate that B3galt2 plays an important role in cognitive function, neuronal maintenance and synaptic plasticity in the adult mouse brain. This study suggests that genetic and/or pharmacological manipulation of glycosyltransferases may be a novel strategy for elucidating the mechanism of and managing various brain disorders.